Peripheral blood circulation adaptation in finswimmers - Dyakova, E. Y.; Mironov, A. A. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to analyse the peripheral blood circulation in the lower limbs of finswimmers. Subject to the study was an Experimental Group of highly-skilled (Sport Masters and Candidate Sport Masters) finswimmers (n=15 aged 18-23 years) having 9+ years of competitive track records. The Reference Group was composed of 15 volunteers (aged 18-21 years) from the academic body conditioning groups of Tomsk State University.